Bulletins and Supplementary Papers of the British School of Archaeology in Jerusalem, 1922-1931 - Holland, Jessica; Abramsky, Kolya; Irving, Sarah (Council for British Research in the Levant, 2023)
Bulletins and Supplementary Papers of the British School of Archaeology in Jerusalem, 1922-1931 has been republished by the Council for British Research in the Levant (CBRL) in 2023, with a newly commissioned introductory text. CBRL was formed as a merger from the British School of Archaeology in Jerusalem, and the British Institute at Amman for Archaeology and History in 1998. 100 years after their original publication, the republication of these bulletins and newsletters from the founding years of the British School of Archaeology in Jerusalem offers important insights into the history of the institution, and also into the discipline of archaeology in the period of the British Mandate in Palestine.